Peningkatan Performa Pengelolaan Aplikasi Pencari Jodoh di Indonesia - Richard Andrew (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Mobile applications for dating or dating-apps are one of plenty alternatives to increase the probability of matching between men and women. Recent numerous data showed that there are temporary slowdown for marriages. If these things continue in several years ahead, it might decreasing the chance of the country to maintain the demographics bonuses as one of country wellknown competitive advantages. However, the usage of dating-apps to enhance the chance of matching still unfamiliar within several people in this country. The research objective is to enhance the dating apps performance through its management. The research is using literature study as the main method. The findings show several ways to develop the dating apps performances and these include the addition of new crowdsourcing method, new product features, the product safety enhancer and the market development. This three findings might implied the dating apps manager should review and evaluate their apps periodically to maintain their beneficiaries.